The effect of real exchange rate changes on labour productivity growth - Gavin Murphy; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2012)
We examine the effect of changes in international competitiveness on labour productivity growth through three channels: (i) export, (ii) import, and (iii) import competition. Using micro data from the Irish manufacturing over the period 1995-2002, we account for firms' heterogeneity in their exposure to international competitive pressure. Our econometric estimates indicate that a real exchange rate appreciation had a negative effect on labour productivity growth once a firm's export exposure was greater than 14 per cent. When a firm's import exposure exceeded 33 per cent, a real exchange rate appreciation had a positive effect on labour productivity. An increase in import competition due to a real exchange rate appreciation had no effect on a firm's labour productivity growth.
Keywords: F12; F41; F43; 330; International competitiveness; Productivity; Firm heterogeneity